Islam dan Marxisme: Pergolakan Wacana Pergerakan di Indonesia - Adam, Ronald (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2025)
This article reviews Lin Hongxuan’s book Ummah Yet Proletariat: Islam, Marxism, and the Making of the Indonesian Republic (2023). The book explores the complex relationship between Islam and Marxism in the Dutch East Indies from 1915 to 1965, highlighting both their compatibility and the gradual shifts in their interactions. Rather than focusing on organizational relations, the book examines diverse forms of movement print culture—including newspapers, books, speeches, memoirs, and novels—which collectively reflect the progressive discourse surrounding the intersections of Islam and Marxism in the Dutch East Indies. The central questions raised are: To what extent are Islam and Marxism compatible? Under what conditions did compromises between them emerge? And how were these compromises articulated? The book argues that the relationship between Islam and Marxism was neither final nor static, as it is often imagined today, but instead dynamic and mutually contested. It further demonstrates that attempts to reconcile Islam with Marxist ideas were diverse and multifaceted.